Is the social representation of nanotechnology anchored in that of GMOs?. Issue 10 (3rd October 2018) - Brunel, Maïté; Launay, Céline; Le Floch, Valérie; Py, Jacques; Cascino, Nadine; Zorapapillan, Méliné; Lo Monaco, Gregory
Abstract : The use of nanotechnology (devices/materials composed of parts less than 10 nanometres) in the development of new products is rapidly expanding. Industrialists and decision-makers consider nanotechnology to be the next industrial revolution, but fear they risk the same resistance to nanotechnology that their counterparts experienced with genetically modified organisms (GMOs). Although risk perception studies have shown that perceived risk of GMOs is quite high compared to that related to nanotechnology, no study to date has explored a potential direct social representation link between the two. The present study aims to fill that gap by comparing the social representations of nanotechnology and GMOs among a population of non-experts. This study was conducted with 282 students in human and social sciences and natural sciences. Using a free association task with the inductive words 'nanotechnology' and 'GMO (genetically modified organism)', we identified the existing social representations of the two based on a structural approach. While the representation of GMOs is objectified in the field of agriculture, objectification for nanotechnology seems to still be lacking, although its possible objectification likely lies in computing and robotics. Our calculation of the rate of similarity of associative words with nanotechnology and GMOs indicated no present, direct link between their social representations. We discuss the possible evolution of the social representation of nanotechnology over time.